Entropy-Based Optimization of 3d-Printed Microchannels for Efficient Heat Dissipation - Martinez-Gutierrez, V; Vasco-Calle, D; Lozano-Steinmetz, F (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Microchannel heat sinks (MCHSs) have emerged as an alternative for dissipating high heat rates. However, manufacturing MCHSs can be expensive, so exploring low-cost additive manufacturing using 3D printing is warranted. Before fabrication, the entropy minimization method helps to optimize MCHSs, enhancing their cooling capacity while maintaining their power consumption. We employed this method through computational simulation of laminar water flow in rectangular microchannels ((Formula presented.) C) and minichannels (mC), considering two heat fluxes (10 and 50 kW/m2). The results showed that the frictional entropy is only appreciable in the smallest and largest channels. These computational results enabled the fabrication of the optimal (Formula presented.) C and mC, whose experimental implementation validated the computational findings. Moreover, we computationally studied the effect of using rGO-Ag water-based nanofluids as a coolant. In general, a reduction in total entropy generation was observed at a heat flux of 50 kW/m2. Although at lower heat flux (10 kW/m2), mC was the best option. Channels with lower heights were more effective at higher heat fluxes (≥50 kW/m2). Our findings offer a cost-effective strategy for fabricating high-performance cooling systems while also highlighting the interplay among heat flux, entropy generation, and nanofluid-enhanced cooling. © 2025 by the authors.